PENGARUH CITRA MEREK DAN WORD OF MOUTH COMMUNICATION TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN TOYOTA RUSH (Studi pada PT. Hadji Kalla Cabang Alauddin Makassar) - Ansir Launtu (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2019)
Influence of Brand Image and Word of Mouth Communication Consumer Purchase Decision Against Toyota Rush in PT. Hadji Kalla Makassar Branch Aluddin. by Mr. Ansir Launtu. This study aims to This research is to test and analyze influence Brand Image and Word Of Mouth Communication on consumer purchase decisions on the Toyota Rush PT. Hadji Kalla Branch Alauddin Makassar.Collecting data using primary data obtained from questionnaires by using random sampling. The population is all consumers who have ever made a purchase in a specified timeframe starting from the year 2014 to 2017 as many as 894 people, whereas samples taken amounted to 90 respondents. The results of the questionnaire have been tested for validity and realibilitasnya, also has tested the assumptions of classical form of normality test and multicollinearity. Methods of data analysis using regression techniques.The results showed that in the proposed hipotesi acceptable because test results were positive and significant hypotheses. This means that the brand image and word of mouth communication positive and significant impact on the desperation of purchase